Enhancing Uptake of Nature-Based Solutions for Informing Coastal Sustainable Development Policy and Planning: A Malaysia Case Study - Chee, Su Yin; Firth, Louise B.; Then, Amy Yee-Hui; Yee, Jean Chai; Mujahid, Aazani; Affendi, Yang Amri; Amir, A. Aldrie; Lau, Chai Ming; Ooi, Jillian Lean Sim; Quek, Yew Aun; Tan, Choo Eng; Yap, Tzuen Kiat; et al. (Frontiers in Ecology and Evolution, 2021)
Nature-based Solutions (NbS) have been advocated to protect, sustainably manage, and restore natural or modified ecosystems, simultaneously providing human well-being and biodiversity benefits. The uptake of NbS differs regionally with some countries exhibiting greater uptake than others. The success of NbS also differs regionally with varying environmental conditions and social-ecological processes. In many regions, the body of knowledge, particularly around the efficacy of such efforts, remains fragmented. Having an “inventory” or “tool box” of regionally-trialed methods, outcomes and lessons learnt can improve the evidence base, inform adaptive management, and ultimately support the uptake of NbS. Using Malaysia as a case study, we provide a comprehensive overview of trialed and tested NbS efforts that used nature to address societal challenges in marine and coastal environments (here referring to mangroves, seagrass, coral reefs), and detailed these efforts according to their objectives, as well as their anticipated and actual outcomes. The NbS efforts were categorised according to the IUCN NbS approach typology and mapped to provide a spatial overview of IUCN NbS effort types. A total of 229 NbS efforts were collated, representing various levels of implementation success. From the assessment of these efforts, several key actions were identified as a way forward to enhance the uptake of Nature-based Solutions for informing coastal sustainable development policy and planning. These include increasing education, training, and knowledge sharing,; rationalizing cooperation across jurisdictions, laws, and regulations; enhancing environmental monitoring; leveraging on existing policies; enabling collaboration and communication; and implementing sustainable finance instruments. These findings can be used to inform the improved application and uptake of NbS, globally.